The Effect of Organizational Culture on Achievement Motivation of Teachers in SMP (Junior High School) Muhammadiyah in Medan - Elfrianto Elfrianto (Budapest International Research and Critics University, 2020)
This study aims to find out the effect of organizational culture on achievement motivation of teachers in SMP (Junior High School) Muhammadiyah in Medan. This research is a quantitative study with ex post facto research design that is the variables studied are not controlled and manipulated by researchers, but the facts are expressed based on the measurement of symptoms that have been held or test what will happen. ). This research is carried out in SMP (junior high school) Muhammadiyah in Medan, which consisted of 13 schools. The results shows that Organizational culture has a direct positive effect on achievement motivation of teachers in SMP (junior high school) Muhammadiyah in Medan. In other words, the stronger the organizational culture, the higher the achievement motivation of teachers in SMP (junior high school) Muhammadiyah in Medan.